Promising Effects of Casearins in Tumor-Bearing Mice and Antinociceptive Action against Oncologic Pain: Molecular Docking and In Vivo Findings - Jurandy do Nascimento Silva; José Ivo Araújo Beserra Filho; Boris Timah Acha; Fernanda Regina de Castro Almeida; Emanuelle Karine Frota Batista; Valdenizia Rodrigues Silva; Larissa Mendes Bomfim; Milena Botelho Pereira Soares; Daniel Pereira Bezerra; André Gonzaga dos Santos; Francisco das Chagas Pereira de Andrade; Anderson Nogueira Mendes; et al. (MDPI AG, 2024)
Safer analgesic drugs remain a hard challenge because of cardiovascular and/or gastrointestinal toxicity, mainly. So, this study evaluated in vivo the antiproliferative actions of a fraction with casearins (FC) from Casearia sylvestris leaves against human colorectal carcinomas and antihyperalgesic effects on inflammatory- or opiate-based pain relief and oncologic pain in Sarcoma 180 (S180)-bearing mice. Moreover, docking investigations evaluated the binding among Casearin X and NMDA(N-methyl-D-aspartate)-type glutamate receptors. HCT-116 colorectal carcinoma-xenografted mice were treated with FC for 15 days. Antinociceptive assays included chemically induced algesia and investigated mechanisms by pharmacological blockade. Intraplantar region S180-bearing animals received a single dose of FC and were examined for mechanical allodynia and behavior alterations. AutoDock Vina determined molecular interactions among Cas X and NMDA receptor subunits. FC reduced tumor growth at i.p. (5 and 10 mg/kg) and oral (25 mg/kg/day) doses (31.12-39.27%). FC reduced abdominal pain, as confirmed by formalin and glutamate protocols, whose antinociception activity was blocked by naloxone and L-NAME (neurogenic phase) and naloxone, atropine, and flumazenil (inflammatory phase). Meanwhile, glibenclamide potentiated the FC analgesic effects. FC increased the paw withdrawal threshold without producing changes in exploratory parameters or motor coordination. Cas X generated a more stable complex with active sites of the NMDA receptor GluN2B subunits. FC is a promising antitumor agent against colorectal carcinomas, has peripheral analgesic effects by desensitizing secondary afferent neurons, and inhibits glutamate release from presynaptic neurons and/or their action on cognate receptors. These findings emphasize the use of clerodane diterpenes against cancer-related pain conditions.